Budgetary analysis of the public policy on science, technology and innovation as a means to assess their effectiveness: the case of the state of Espírito Santo in the period 2012 – 2015 - Salles, Felipe; Grassi, Robson (Geografares, 2018)
The article evaluates the public policy of science, technology and innovation (STI) of the Government of the State of Espírito Santo, in the period 2012-2015, by analyzing the elaboration and execution of the budget, based on data from the Pluriannual Plan of that period. Based on theoretical and methodological analysis of STI and public budget components, the financial performance of the STI programs and actions is evaluated in order to identify the priority axes of public policy and its execution in budgetary terms. It is shown that substantial expenditures in the period were carried out with actions focused on the areas of work and professional education, which reveal a lack of focus of the policy, besides evidencing the strong disproportion of the volume of resources destined to scientific research to the detriment of the productive sector, facts that show the need for course corrections regarding how a mature system of STI works. This means that the detailed analysis of budget elaboration and execution, besides proving an important source of data on STI public policies, are fundamental requirements for the improvement of the policy for these areas, since they allow a greater refinement both in the planning and execution of such policy. The State of Espírito Santo, despite the efforts of the last governments, still presents indicators of STI that show a great delay in relation to the more developed states. Thus, it is concluded that, in order to elaborate an authentic state policy for the areas of STI, in addition to providing more resources, a minimum of strategic planning and active governmental coordination is necessary for these areas, and the analysis of budget preparation and execution should be an integral part of this process.